Anti-carbon deposition high-stability organic liquid hydrogen storage material hydrogenation catalyst and preparation method and application thereof

By doping rare earth metal oxides into nickel-based catalysts, hydrogenation catalysts for high-stability organic liquid hydrogen storage materials are prepared, which solves the problem of insufficient stability of nickel-based catalysts and achieves the effect of long-term stable use in industrial applications.

CN119857487AActive Publication Date: 2025-04-22CHINA UNIV OF GEOSCIENCES (WUHAN)

Patent Information

Application Number
CN202510104815.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-22
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Nickel-based catalysts are insufficient in the hydrogenation process of organic liquid hydrogen storage materials, which easily leads to a decrease in activity due to carbon accumulation and affects service life.

Method used

The active metal Ni and rare earth metal oxide additives were supported on the support by co-precipitation method to prepare a hydrogenation catalyst for an organic liquid hydrogen storage material that resists carbon deposits and has high stability. Rare earth metal oxides such as CeO2, Y2O3 or Eu2O3 form oxygen vacancy on the catalyst surface, inhibiting carbon deposits and enhancing catalyst stability.

Benefits of technology

Without using precious metals, the prepared catalyst exhibits good activity and stability, and can maintain more than 90% of the primary activity after 10 cycles, significantly improving the catalyst's anti-carbon deposit performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857487A_ABST
    Figure CN119857487A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an anti-carbon deposition high-stability organic liquid hydrogen storage material hydrogenation catalyst, and the hydrogenation catalyst is obtained by loading an active metal Ni and a rare earth metal oxide auxiliary agent on a carrier through a coprecipitation method. According to the hydrogenation catalyst prepared by the invention, the adsorption capacity of the catalyst and the dispersity of active metal components are enhanced by utilizing the carrier with high specific surface area, and the catalytic performance is effectively improved; meanwhile, the introduction of the rare earth metal oxide modifier optimizes the reaction path, the formation of carbon deposition is effectively inhibited by forming oxygen vacancies and improving the lattice oxygen migration rate, and the carbon deposition resistance and the cycle stability of the catalyst are remarkably enhanced. The preparation method of the hydrogenation catalyst provided by the invention is mild in process and simple in required equipment, and can be used for large-scale production. Besides, the catalyst still has relatively high activity, stability and cycle performance without using noble metal, has good economic benefits and also has wide popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogenation catalysts, and specifically relates to a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst and a preparation method thereof, and also relates to the application of the catalyst in catalytic dehydrogenation of organic liquids. Background Art

[0002] Organic liquid hydrogen storage technology is one of the most promising hydrogen storage technologies to solve the problem of hydrogen storage and transportation. The development of efficient, stable and economical hydrogenation catalysts for organic liquid hydrogen storage materials is the key to promoting the development of this technology. Currently, commercial catalysts for hydrogenation of organic liquid hydrogen storage materials on the market usually use precious metals such as Ru and Rh as active components, and their high cost limits their widespread adoption in industrial applications. In contrast, non-precious metal Ni has abundant reserves and low cost, making it a good choice to replace precious metals such as Ru and Rh.

[0003] Patent CN112675865A discloses a supported nickel-based catalyst, which exhibits good activity for the catalytic hydrogenation of NPCZ at 150°C and a hydrogen pressure of 7MPa. However, after five cycles of use, its activity decreased. Patent CN 117599806 A discloses a nano-confined Ni Ru metal catalyst, which has a reduced catalytic activity during the fifth cycle of use, specifically, the completion time of the hydrogenation reaction is extended from 60 minutes in the first cycle to 180 minutes. The above phenomenon shows that although the modified nickel-based catalyst has a catalytic activity comparable to that of precious metal catalysts, its stability improvement still faces great challenges.

[0004] Carbon deposition is one of the key factors that lead to the deactivation of nickel-based catalysts. During the hydrogenation process of organic liquid hydrogen storage materials, the side reaction of molecular CC bond breaking often occurs, resulting in the formation of carbonaceous deposits on the catalyst surface, which covers a large number of catalyst active sites and significantly reduces the life of the catalyst. γ It is the most stable and difficult to remove form of carbon. In view of this, researchers have been actively researching and developing methods to remove C from the surface of nickel-based catalysts. γ Carbon deposition strategy.

[0005] In summary, although nickel-based catalysts can show comparable activity to precious metal catalysts in the hydrogenation of organic liquid hydrogen storage materials, the improvement of their stability is the key to their widespread adoption in industrial applications. Therefore, providing a new modification method for nickel-based catalysts to increase the catalyst's rate of removing carbon deposits and inhibit the occurrence of CC bond rupture side reactions is of great significance for effectively improving the stability and service life of the catalyst, and is also a technical problem that researchers urgently need to solve. Summary of the invention

[0006] One of the purposes of the present invention is to provide a method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst with mild preparation process and simple required equipment.

[0007] A second object of the present invention is to provide a high-stability organic liquid hydrogen storage material hydrogenation catalyst that is resistant to carbon deposition.

[0008] The third object of the present invention is to provide an application of a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, which can exhibit good activity and stability in the hydrogenation of organic liquid hydrogen storage materials without using precious metals.

[0009] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, comprising the following steps: S1, dissolving a nickel salt, a carrier metal salt and a rare earth metal salt in water to obtain a first solution; dissolving a precipitant and a complexing agent in water respectively to obtain a second solution and a third solution; S2. In a water bath, slowly dropwise add the first solution and the second solution to the third solution simultaneously, stirring continuously to form a precipitate; separating and washing the precipitate to obtain a first product; S3, dispersing the first product in anhydrous ethanol, and then removing the solvent to obtain a second product; S4, grinding the second product to obtain a powder, and calcining the powder to obtain a catalyst precursor; S5. Placing the catalyst precursor under a reducing atmosphere for reduction treatment, cooling it, and then performing a passivation treatment to obtain a hydrogenation catalyst.

[0010] The rare earth metal salt is selected from any one or more combinations of soluble metal salts corresponding to rare earth metals Ce, Y or Eu; in the hydrogenation catalyst, the loading amount of metal nickel is 20wt.%-50wt.%, and the doping amount of rare earth metal oxide is 1wt.%-10wt.%.

[0011] The overall idea and inventive principle of the present invention are as follows: Rare earth metal oxides such as cerium oxide, europium oxide, and yttrium oxide have unique oxygen storage capacity, which can store and release oxygen species on the catalyst surface, helping to increase the catalyst's rate of eliminating carbon deposits; at the same time, the addition of rare earth metal oxides will optimize the reaction path and inhibit the occurrence of side reactions such as CC bond rupture. These characteristics make doping rare earth metal oxides into nickel-based catalysts a new strategy to increase catalyst life. Therefore, the preparation method of the hydrogenation catalyst provided by the present invention loads the active metal Ni and the rare earth metal oxide additive on a carrier by a coprecipitation method to prepare a hydrogenation catalyst that exhibits good activity and stability for the hydrogenation of organic liquid hydrogen storage materials without the use of precious metals.

[0012] Furthermore, it has been found through research that although different types of rare earth metal oxides have a certain oxygen storage capacity, the temperature at which oxygen vacancies are formed is different. For example, La2O3 is easy to produce oxygen vacancies at high temperatures (about 750°C), and high temperature treatment easily leads to agglomeration of Ni nanoparticles. After screening and comparison, the present invention uses soluble metal salts corresponding to rare earth metals Ce, Y or Eu as rare earth metal salts, and the CeO2, Y2O3 or Eu2O3 doped in the hydrogenation catalyst is prepared. 3, Oxygen vacancies can be formed at relatively low temperatures (300-350°C), and their oxygen storage capacity can be used to remove carbon deposits. In addition, CeO2, Y2O3 or Eu2O3 can prevent Ni nanoparticles from being covered. When the loading amount of metal nickel in the hydrogenation catalyst is controlled to be 20wt.%-50wt.%, and the doping amount of rare earth metal oxide is 1wt.%-10wt.%, it has a better anti-carbon deposition effect and further improves the cycle stability of the catalyst.

[0013] Preferably, in the hydrogenation catalyst, when the loading amount of metal nickel is controlled to be 30wt.%-50wt.%, and the doping amount of rare earth metal oxide is controlled to be 3wt.%-5wt.%, after the hydrogenation catalyst is recycled for 10 times, the catalytic performance is still maintained at more than 90% of the initial use.

[0014] Further, in step S1, the nickel salt includes one or more combinations of Ni(NO3)2·6H2O, NiCl2·6H2O, and NiSO4·6H2O; the carrier metal salt includes one or more combinations of Al (NO3)2·9H2O, Ti(NO3)4, and Mg(NO3)2; Furthermore, the rare earth metal salt includes a combination of one or more of soluble nitrates, soluble sulfates, soluble acetates, and soluble chlorides corresponding to the rare earth metals Ce, Y or Eu; preferably, the rare earth metal salt is selected from any one of Ce(NO3)4, Y(NO3)3·9H2O, and Eu(NO3)3·9H2O.

[0015] Furthermore, in step S1, the precipitant includes a combination of one or more of Na2CO3, K2CO3, NaHCO3, and Na2SO3; the ligand includes a combination of one or more of polyethylene glycol, polydextrose, and polyfructose.

[0016] Among them, the precipitant Ni 2+ 、Ce 4+ , Y 3+ and Eu 3+ Precipitation, the specific reaction equation is as follows: Ni 2+ +CO3 2- →NiCO3↓; Ce 4+ +2CO3 2- +2H2O→Ce(OH)4↓+2CO2↑; 2Y 3+ +3CO3 2- +3H2O→2Y(OH)3↓+3CO2↑; 2Eu 3+ +3CO3 2- +3H2O→2Eu(OH)3↓+3CO2↑.

[0017] The ligand is used to coordinate with the metal ions. Taking polyethylene glycol (PEG) as an example, the oxygen atom in the polyethylene glycol molecule has a lone electron pair, which can coordinate with the metal ions. This coordination effect can make the growth and nucleation process of the catalyst more regular, and it can be removed in the subsequent washing precipitation with water and ethanol to avoid residue.

[0018] Preferably, in step S1, the precipitant is Na2CO3, and the coordination agent is polyethylene glycol (PEG), wherein the polyethylene glycol includes any one of PEG 200, PEG 600, PEG 2000, and PEG 20000.

[0019] Furthermore, in step S2, the temperature of the water bath is 70-100° C.; in step S3, the method of removing the solvent includes: azeotropic evaporation of water and anhydrous ethanol under oil bath conditions at 90-150° C. In step S3, the first product is first dispersed in anhydrous ethanol, and then the solvent is removed, which can disperse the precipitate and prevent large-scale aggregation of precipitate particles, which is conducive to rapid evaporation of the product.

[0020] Furthermore, in step S4, the calcination temperature is 400-800° C. and the calcination time is 1-3 h.

[0021] Furthermore, in step S5, the reducing atmosphere is a mixed gas consisting of an inert gas and hydrogen, and the flow rate of the mixed gas is 50-90 mL / min.

[0022] Furthermore, in step S5, the temperature of the reduction treatment is 550-750° C., and the time is 3-6 hours.

[0023] Further, in step S5, the passivation treatment includes: introducing a mixed gas of an inert gas and oxygen into the cooled product for a time of 0.5-2h. In step S5, the newly prepared Ni catalyst obtained by gas phase reduction is prone to severe oxidation or even combustion when directly exposed to the air due to its small particle size and relatively active chemical properties. After the catalyst is cooled to room temperature, the introduction of a mixed gas of an inert gas and O2 can cause the surface of the Ni catalyst to be slowly oxidized, forming a layer of nickel oxide film on the surface to prevent Ni from further oxidation.

[0024] The technical solution adopted by the present invention to achieve the second purpose is: to provide a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, which is prepared by the preparation method according to one of the purposes of the present invention; the specific surface area of ​​the hydrogenation catalyst is 100-400m 2 / g, pore volume is 0.2-1.4cm 3 / g, pore size is 5-25nm.

[0025] The hydrogenation catalyst prepared by the present invention uses one of Al2O3, TiO2, and MgO as a carrier, is doped with one of rare earth metal oxides CeO2, Y2O3, and Eu2O3 as a modifier, and uses metal nickel as an active component. In the hydrogenation catalyst, the loading amount of metal nickel is 20wt.%-50wt.%, the particle size of metal nickel is 5-15nm, and the doping amount of rare earth metal oxide is 1wt.%-10wt.%.

[0026] The hydrogenation catalyst prepared by the present invention has a good physical structure: on the one hand, a carrier with a high specific surface area is used to load the active metal Ni, and the high specific surface area has a positive effect on the catalytic activity of the active component and the adsorption of reactants and gases; on the other hand, the rare earth metal oxides CeO2, Y2O3, and Eu2O3 have the functions of forming oxygen vacancies and improving the migration rate of lattice oxygen, which effectively inhibits the formation of carbon deposits in the catalytic process and further improves the catalytic stability.

[0027] The technical solution adopted by the present invention to achieve the third purpose is: to provide an application of the carbon deposition resistant and high-stability organic liquid hydrogen storage material hydrogenation catalyst according to the second purpose of the present invention, and to use the carbon deposition resistant and high-stability organic liquid hydrogen storage material hydrogenation catalyst for the hydrogenation reaction of the organic liquid hydrogen storage material, wherein the organic liquid hydrogen storage material includes a combination of one or more of N-propylcarbazole, N-ethylcarbazole, toluene, dibenzyltoluene, 1-methylindole, and 1,2-dimethylindole.

[0028] Furthermore, the application conditions include: mixing the hydrogenation catalyst and the organic liquid hydrogen storage material in a mass ratio of 1:(5-15), then adding 1,4-dioxane as a solvent, the reaction pressure is 6-8MPa, the reaction temperature is 130-170°C, and the stirring speed is 500-700rpm / min.

[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst provided by the present invention is to load active metal Ni and rare earth metal oxide additives on a carrier by a coprecipitation method, thereby preparing a hydrogenation catalyst that exhibits good activity and stability for hydrogenation of organic liquid hydrogen storage materials without using precious metals. The preparation method provided by the present invention has a mild process, simple equipment, and can be used for large-scale production. The catalyst prepared by the present invention has high activity and stability without using precious metals, and has good economic benefits.

[0030] (2) The carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst prepared by the present invention has high activity and stability. On the one hand, the present invention utilizes a high specific surface area carrier to enhance the adsorption capacity of the catalyst and the dispersion of the active metal components, thereby effectively improving the catalytic performance. On the other hand, the introduction of a rare earth metal oxide modifier optimizes the reaction pathway, effectively inhibits the formation of carbon deposits by forming oxygen vacancies and increasing the lattice oxygen migration rate, and significantly enhances the catalyst's carbon deposition resistance and cycle stability.

[0031] (3) The rare earth metal oxide doped in the hydrogenation catalyst prepared by the present invention is selected from one of CeO2, Y2O3 or Eu2O3. These rare earth metal oxides can form oxygen vacancies at relatively low temperatures, and their oxygen storage capacity is used to remove carbon deposits. In addition, the advantage of CeO2, Y2O3 or Eu2O3 forming oxygen vacancies under low temperature conditions can also prevent Ni nanoparticles from being covered, thereby improving the anti-carbon deposition effect and further improving the cycle stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 N2 physical adsorption-desorption curve of the hydrogenation catalyst prepared in Example 1; Figure 2 This is the pore size distribution diagram of the hydrogenation catalyst prepared in Example 1; Figure 3 A transmission electron microscope image of the hydrogenation catalyst prepared in Example 1; Figure 4 The particle size distribution diagram of the hydrogenation catalyst prepared in Example 1; Figure 5The distribution curve of the hydrogenation product distribution of N-propylcarbazole (NPCZ) prepared by the hydrogenation catalyst in Example 1 over time; Figure 6 The curve showing the change of hydrogen absorption over time of NPCZ after 10 hydrogenation cycles catalyzed by the hydrogenation catalyst prepared in Example 1; Figure 7 TG graph after 10 cycles of NPCZ catalyzed by the hydrogenation catalyst prepared in Example 1; Figure 8 The DSC graph of the hydrogenation catalyst prepared in Example 1 after catalyzing NPCZ for 10 cycles; Fig. 9 The Raman graph of the hydrogenation catalyst prepared in Example 1 after 10 cycles of NPCZ reaction; Fig.10 The distribution curve of the hydrogenation product distribution of NPCZ by the hydrogenation catalyst prepared in Comparative Example 1 changes with time; Fig.11 The curve showing the change of hydrogen absorption over time of NPCZ after 10 hydrogenation cycles catalyzed by the hydrogenation catalyst prepared in Comparative Example 1; Fig.12 This is the TG graph after 10 cycles of NPCZ catalyzed by the hydrogenation catalyst prepared in Comparative Example 1; Fig.13 The DSC graph of the hydrogenation catalyst prepared in Comparative Example 1 after catalyzing NPCZ for 10 cycles; Fig.14 The Raman graph of the hydrogenation catalyst prepared in Comparative Example 1 after 10 cycles of NPCZ reaction; Fig.15 The curves of hydrogen absorption during ten hydrogenation reactions of NPCZ catalyzed by the hydrogenation catalysts prepared in Examples 1-6 and Comparative Examples 1-5 (each hydrogenation reaction lasts 120 min). DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0035] The embodiment of the present invention provides a method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, comprising the following steps: Step 1: dissolving a nickel salt, a carrier metal salt and a rare earth metal salt in water to obtain a first solution; dissolving a precipitant and a complexing agent in water respectively to obtain a second solution and a third solution; Wherein, the rare earth metal salt is selected from any one of Ce(NO3)4, Y(NO3)3·9H2O, Eu(NO3)3·9H2O; the nickel salt includes one or more combinations of Ni(NO3)2·6H2O, NiCl2·6H2O, NiSO4·6H2O; the carrier metal salt includes any one of Al (NO3)2·9H2O, Ti(NO3)4, Mg(NO3)2; the precipitant includes one or more combinations of Na2CO3, K2CO3, NaHCO3, Na2SO3; the ligand includes one or more combinations of polyethylene glycol, polydextrose, and polyfructose.

[0036] Step 2: In a water bath at 70-100° C., the first solution and the second solution are slowly added dropwise to the third solution simultaneously, and stirred continuously to form a precipitate; the precipitate is separated and washed to obtain a first product.

[0037] Step 3: Disperse the first product in anhydrous ethanol, and then remove the solvent by azeotropic evaporation of water and anhydrous ethanol under oil bath conditions at 90-150° C. to obtain the second product.

[0038] Step 4: Grind the second product to obtain powder, and calcine the powder at a temperature of 400-800° C. for 1-3 hours to obtain a catalyst precursor.

[0039] Step 5: placing the catalyst precursor under a reducing atmosphere for reduction treatment at a temperature of 550-750°C for 3-6 hours; introducing a mixed gas of inert gas and oxygen into the cooled product for 0.5-2 hours for passivation treatment to obtain a hydrogenation catalyst; in the hydrogenation catalyst, the loading amount of metal nickel is 20wt.%-50wt.%, and the doping amount of rare earth metal oxide is 1wt.%-5wt.%.

[0040] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0041] The main parameters and experimental conditions involved in the embodiments and comparative examples of the present invention are shown in Table 1 below: Table 1

[0042] Example 1 A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, comprising the following steps: (1) Weigh 7.4320 g of Ni(NO3)2·6H2O, 0.7439 g of Ce(NO3), and 12.3400 g of Al(NO3)3·9H2O and dissolve them in deionized water to form solution A'; weigh 15.7826 g of Na2CO3 and dissolve it in deionized water to form solution B'; weigh 0.5 g of PEG2000 and dissolve it in deionized water to form solution C'; (2) In a 90°C water bath, slowly add solution A' and solution B' to solution C' at the same time, stirring continuously to form a light green precipitate. After filtering the precipitate, wash the precipitate continuously with deionized water and anhydrous ethanol until the eluate is neutral; (3) dispersing the precipitate obtained in step (2) in anhydrous ethanol, and azeotropically evaporating water and anhydrous ethanol in an oil bath at 120°C; (4) The obtained solid was ground into powder and then calcined in a muffle furnace at 600 °C for 1 h. After cooling to room temperature, a dark green powder catalyst precursor was obtained; (5) The catalyst precursor powder in step (4) was transferred to a tubular furnace, and Ar / H2 mixed gas A (H2 volume content of 10%, gas flow rate of 70 ml / min) was introduced. After calcination at 650°C for 6 h, it was allowed to cool to room temperature. Then, Ar / O2 mixed gas B (O2 volume content of 1%, gas flow rate of 70 ml / min) was introduced for passivation for 1 h to obtain a Ni / CeO2-Al2O3 catalyst supported on a CeO2 and Al2O3 composite carrier, wherein the theoretical loading amount of Ni was 30 wt%, the theoretical doping amount of CeO2 was 5 wt%, and the catalyst was recorded as Ni30 / Ce5Al.

[0043] The physical adsorption-desorption curve of Ni30 / Ce5Al catalyst is shown in Figure 1 As shown, the pore size distribution is Figure 2 As shown, from Figure 1 It can be seen that the Ni30 / Ce5Al catalyst exhibits a type IV adsorption isotherm, indicating that the prepared sample forms a mesoporous structure and the specific surface area of ​​the catalyst is 322 m 2 / g, Figure 2 The distribution of the catalyst pore structure was further explained. The Barrett-Joyner-Halenda (BJH) calculation method was used to calculate the catalyst pore volume to be 1.26 cm 3 / g, and the average pore size is 14.50nm.

[0044] The transmission electron microscopy image of the catalyst is as follows Figure 3 As shown, from Figure 3 It can be seen that the active metal nickel is highly dispersed on the catalyst surface in the form of nanocluster particles. The particle size distribution diagram of the catalyst is as follows Figure 4 As shown, from Figure 4 It can be seen that the average particle size of the novel catalyst is 9.91 nm.

[0045] Example 2 A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, the steps are as in Example 1; the main difference from Example 1 is that the raw materials weighed in step (1) are 6.08g NiCl2·6H2O, 10.73g Ti(NO3)4, 0.7446g Y(NO3)3·9H2O, 13.8744g Na2CO3 is weighed, and 0.5g PEG200 is used to dissolve in deionized water to form a solution C'. The prepared catalyst is Ni30 / Y5Ti.

[0046] Example 3 A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, the steps are as in Example 1; the main difference from Example 1 is that the raw materials weighed in step (1) are 6.72 g NiSO4·6H2O, 11.99 g Mg(NO3)2, 0.7446 g Eu(NO3)3·9H2O, 13.8378 g Na2CO3 is weighed, and 0.5 g PEG600 is used to dissolve in deionized water to form a solution C'. The obtained catalyst is Ni30 / Eu5Mg.

[0047] Example 4 A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, the steps are as in Example 1: The main difference from Example 1 is that the raw materials weighed in step (1) are nickel nitrate hexahydrate Ni(NO3)2·6H2O: 7.4320 g, aluminum nitrate nonahydrate Al(NO3)3·9H2O: 12.1900 g, cerium nitrate Ce(NO3)40.4463 g, and anhydrous sodium carbonate Na2CO3 weighed 16.0090 g. 0.5 g PEG2000 is dissolved in deionized water to form solution C'. The catalyst is recorded as Ni30 / Ce3Al.

[0048] Example 5 A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, the steps are as in Example 1: The main difference from Example 1 is that the raw materials weighed in step (1) are nickel nitrate hexahydrate Ni(NO3)2·6H2O: 7.4320 g, aluminum nitrate nonahydrate Al(NO3)3·9H2O: 11.020 g, cerium nitrate Ce(NO3)41.4878 g, and anhydrous sodium carbonate Na2CO3 weighed 15.2165 g. 0.5 g PEG2000 is dissolved in deionized water to form solution C'. The catalyst is recorded as Ni30 / Ce10Al.

[0049] Example 6 A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, the steps are as in Example 1: The main difference from Example 1 is that the raw materials weighed in step (1) are nickel nitrate hexahydrate Ni(NO3)2·6H2O: 12.38g, aluminum nitrate nonahydrate Al(NO3)3·9H2O: 8.31g, cerium nitrate Ce(NO3)40.7439g, and anhydrous sodium carbonate Na2CO3 weighed 14.2074g. 0.5g PEG2000 is dissolved in deionized water to form solution C'. The catalyst is recorded as Ni50 / Ce5Al.

[0050] Comparative Example 1 A method for preparing a hydrogenation catalyst Ni30 / Al2O3, the steps are the same as those of Example 1; the difference is that the raw materials weighed in step (1) of Comparative Example 1 are 7.4320 g of Ni(NO3)2·6H2O and 25.77 g of Al(NO3)3·9H2O. The weight of Na2CO3 is 16.3579 g. The catalyst is recorded as Ni30 / Al2O3.

[0051] Comparative Example 2 A method for preparing a hydrogenation catalyst Ni30 / TiO2, the steps are the same as those of Example 2; the difference is that the raw materials weighed in step (1) of Comparative Example 2 are 6.0749 g NiCl2·6H2O, 12.9665 g Ti(NO3)4, 14.3982 g Na2CO3 is weighed, and 0.5 g PEG200 is dissolved in deionized water to form a solution C'. The prepared catalyst is Ni30 / TiO2.

[0052] Comparative Example 3 A method for preparing a hydrogenation catalyst Ni30 / MgO, the steps are the same as those of Example 3; the difference is that the raw materials weighed in step (1) of Comparative Example 3 are 6.7179 g NiSO4·6H2O, 12.8796 g Mg(NO3)2, 14.2957 g Na2CO3, and 0.5 g PEG600 is dissolved in deionized water to form a solution C'. The obtained catalyst is Ni30 / MgO.

[0053] Comparative Example 4 A method for preparing a hydrogenation catalyst Ni10 / Ce5Al, the steps are the same as those of Example 1; the difference is that the raw materials weighed in step (1) of Comparative Example 4 are 2.4700 g of nickel nitrate hexahydrate Ni(NO3)2·6H2O, 15.6500 g of aluminum nitrate nonahydrate Al(NO3)3·9H2O, 0.7439 g of cerium nitrate Ce(NO3), and 17.3578 g of anhydrous sodium carbonate Na2CO3. 0.5 g of PEG2000 is dissolved in deionized water to form a solution C'. The catalyst is recorded as Ni10 / Ce5Al.

[0054] Comparative Example 5 A method for preparing a hydrogenation catalyst Ni70 / Ce5Al, the steps are as in Example 1; the difference is that the raw materials weighed in step (1) of Comparative Example 5 are 17.28 g of nickel nitrate hexahydrate Ni(NO3)2·6H2O, 4.61 g of aluminum nitrate nonahydrate Al(NO3)3·9H2O, 40.7439 g of cerium nitrate Ce(NO3), and 12.6323 g of anhydrous sodium carbonate Na2CO3. 0.5 g of PEG2000 is dissolved in deionized water to form a solution C'. The catalyst is recorded as Ni70 / Ce5Al.

[0055] Application performance testing Take 0.2 g of the catalyst prepared in Example 1, 2.0 g of NPCZ as the hydrogen storage material, add 40 ml of n-hexane as the solvent, the reaction pressure is 7 MPa, the reaction temperature is 150°C, the rotation speed is 600 rpm / min, and the reaction time is 25 min to achieve complete hydrogenation of NPCZ without other by-products. The catalyst has the following effects on the hydrogenation reaction components of NPCZ: Figure 5 As shown, from Figure 5 It can be seen that the Ni30 / Ce5Al catalyst prepared in Example 1 completed hydrogenation within 25 minutes.

[0056] The 10 cyclic hydrogenation experiments of the catalyst were all carried out at 150°C and 7MPa. After each hydrogenation, the catalyst was not treated in any way for the next experiment. The curve of hydrogen absorption over time for the 10 hydrogenation experiments is shown in Figure 2. Figure 6 As shown, after 10 cycles of hydrogenation reaction, the Ni30 / Ce5Al catalyst prepared in Example 1 can still achieve complete hydrogenation of NPCZ within 120 minutes, indicating that the catalyst has good stability and can be recycled for multiple times.

[0057] The TG results of the catalyst after cycling are as follows: Figure 7 As shown, the test atmosphere is air, the weight loss rate of the catalyst is 8.79%, and the carbon deposit types are tested and analyzed using DSC. The results are as follows Figure 8 As shown, the amount of graphite carbon deposition on the Ni30 / Ce5Al catalyst above 500°C is small, indicating that the formation of graphite carbon on the Ni30 / Ce5Al catalyst is suppressed during the catalytic process.

[0058] The properties and structure of the carbonaceous material formed on the catalyst prepared in Example 1 after 10 cycles were studied by Raman spectroscopy. The ID / IG of the Ni30 / Ce5Al catalyst prepared in Example 1 was 1.09, and the carbon deposits had a low degree of graphitization and were easier to remove.

[0059] The performance test process of the Ni30 / Al2O3 catalyst prepared in Comparative Example 1 is the same as that in Example 1. The catalyst has a hydrogenation reaction effect on NPCZ components such as Fig.10 As shown in FIG. 1 , the Ni / Al2O3 catalyst completed hydrogenation within 60 min. The stability test of the Ni30 / Al2O3 catalyst prepared in Comparative Example 1 was the same as that in Example 1. The curve of hydrogen absorption over time after 10 hydrogenation cycles is shown in FIG. Fig.11 As shown, the Ni30 / Al2O3 catalyst prepared in Comparative Example 1 can achieve complete hydrogenation within 120 min in the first five reactions, and the catalytic activity decreases significantly starting from the sixth reaction. The hydrogenation amount of the 10th hydrogenation reaction is 3.91 wt%.

[0060] The TG results of the catalyst of Comparative Example 1 after circulation are as follows: Fig.12 As shown, the test atmosphere is air, the weight loss rate of the catalyst is 17.6%, and the carbon deposit types are tested and analyzed using DSC. The results are as follows Fig.13 As shown in Figure 2, there are a large number of C oxidized at 300-500°C in the Ni / Al2O3 catalyst after cycling. β species, thereby affecting the catalytic activity of Ni30 / Al2O3 and deactivating the catalyst.

[0061] The Raman spectrum of the Ni30 / Al2O3 catalyst after cycling is shown in Figure 2. Fig.14 As shown, I D / I G It is 0.88, the carbon on the catalyst surface is highly graphitized, the structure is more ordered, and it is more difficult to remove, which affects the catalytic activity.

[0062] Further, Fig.15 The curves of hydrogen absorption variation of NPCZ catalyzed by the catalysts prepared in Examples 1-6 and Comparative Examples 1-5 after ten hydrogenation reactions (each hydrogenation reaction lasts 120 min) are shown. Table 2 shows the hydrogen absorption of the catalysts prepared in each Example and Comparative Example when first used, the hydrogen absorption in the 10th cycle, and the catalytic performance retention rate of the catalyst after 10 cycles.

[0063] Table 2

[0064] Depend on Fig.15 and Table 2, Based on the test results of Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3, it can be seen that after doping with a certain amount of rare earth metal oxide additives CeO2, Y2O3 or Eu2O3, the catalyst has strong stability and can still maintain a high catalytic activity after 10 hydrogenation cycle experiments, while the unmodified catalyst is significantly deactivated after 10 hydrogenation experiments.

[0065] Based on the test results of Example 1 and Examples 4 and 5, it can be seen that appropriate CeO2 has a positive effect on improving the activity of the catalyst, but excessive CeO2 will reduce the catalytic performance, which may be due to excessive CeO2 blocking the catalyst pores, resulting in a decrease in specific surface area and agglomeration of Ni nanoparticles. Therefore, controlling the doping amount of rare earth metal oxide to 3wt.%-5wt.% helps to further improve the cycle performance of the catalyst.

[0066] Based on the test results of Example 1, Example 5, Comparative Example 4 and Comparative Example 5, it can be seen that when the Ni loading is controlled at 30wt.%-50wt.%, the catalyst has the best activity and stability. This may be because when the Ni loading is low, Ni interacts strongly with the catalyst carrier, forming more NiAl2O4 with high thermal stability, reducing the reduction degree of Ni; while too high Ni loading will cause Ni nanoparticles to agglomerate during the reaction.

[0067] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, characterized in that: The following steps are involved: S1, dissolving nickel salt, carrier metal salt and rare earth metal salt in water to obtain a first solution; Dissolving the precipitant and the complexing agent in water respectively to obtain a second solution and a third solution; S2. In a water bath, slowly dropwise add the first solution and the second solution into the third solution simultaneously, stirring continuously to form a precipitate; separating and washing the precipitate to obtain a first product; S3, dispersing the first product in anhydrous ethanol, and then removing the solvent to obtain a second product; S4, grinding the second product to obtain a powder, and calcining the powder to obtain a catalyst precursor; S5, placing the catalyst precursor under a reducing atmosphere, performing a reduction treatment, cooling and then performing a passivation treatment to obtain a hydrogenation catalyst; The rare earth metal salt is selected from any one or more combinations of soluble metal salts corresponding to rare earth metals Ce, Y or Eu; in the hydrogenation catalyst, the loading amount of metal nickel is 20wt.%-50wt.%, and the doping amount of rare earth metal oxide is 1wt.%-10wt.%.

2. The preparation method according to claim 1, characterized in that In step S1, the nickel salt includes one or more combinations of Ni(NO3)2·6H2O, NiCl2·6H2O, and NiSO4·6H2O; the carrier metal salt includes one or more combinations of Al(NO3)2·9H2O, Ti(NO3)4, and Mg(NO3)2; the rare earth metal salt is selected from any one of Ce(NO3)4, Y(NO3)3·9H2O, and Eu(NO3)3·9H2O.

3. The preparation method according to claim 1, characterized in that: In step S1, the precipitant includes one or more combinations of Na2CO3, K2CO3, NaHCO3, and Na2SO3; the ligand includes one or more combinations of polyethylene glycol, polydextrose, and polyfructose.

4. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the water bath is 70-100°C; in step S3, the method of removing the solvent includes: azeotropically evaporating water and anhydrous ethanol under oil bath conditions at 90-150°C.

5. The preparation method according to claim 1, characterized in that: In step S4, the calcination temperature is 400-800°C and the time is 1-3 hours.

6. The preparation method according to claim 1, characterized in that In step S5, the reducing atmosphere is a mixed gas consisting of an inert gas and hydrogen, and the flow rate of the mixed gas is 50-90 mL / min.

7. The preparation method according to claim 1, characterized in that: In step S5, the reduction treatment is carried out at a temperature of 550-750° C. for 3-6 hours.

8. The preparation method according to claim 1, characterized in that: In step S5, the passivation treatment includes: introducing a mixed gas of an inert gas and oxygen into the cooled product for a time of 0.5-2 hours.

9. A carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8; the specific surface area of ​​the hydrogenation catalyst is 100-400m 2 / g, pore volume is 0.2-1.4cm 3 / g, pore size is 5-25nm.

10. The use of the carbon deposition resistant and highly stable organic liquid hydrogen storage material hydrogenation catalyst according to claim 9, characterized in that: The carbon deposition resistant and high stability organic liquid hydrogen storage material hydrogenation catalyst is used for the hydrogenation reaction of organic liquid hydrogen storage material, and the organic liquid hydrogen storage material comprises a combination of one or more of N-propylcarbazole, N-ethylcarbazole, toluene, dibenzyltoluene, 1-methylindole and 1,2-dimethylindole.

Citation Information

Patent Citations

  • Nano confinement Ni-Ru metal catalyst for hydrogenation as well as preparation method and application of nano confinement Ni-Ru metal catalyst

    CN117599806A

  • High-activity and high-stability supported nickel catalyst as well as preparation method and application thereof

    CN112675865A

  • La modified Ni / Al2O3 catalyst, preparation method and application

    CN113546631A

  • Composite carrier catalyst for dehydrogenation of liquid organic matter hydrogen storage medium and preparation method of composite carrier catalyst

    CN114653357A

  • Ni-based catalyst as well as preparation method and application thereof

    CN115634695A

Cited By

  • High-stability liquid organic hydrogen storage carrier hydrogenation catalytic material as well as preparation method and application thereof

    CN122209407A